Pdlim4 is essential for CCR7‐JNK–mediated dendritic cell migration and F‐actin–related dendrite formation. Issue 10 (9th July 2019) - Yoo, Ji-Young; Jung, Nam-Chul; Lee, Jun-Ho; Choi, So-Yeon; Choi, Hyun-Ji; Park, Soo-Yeoun; Jang, Ji-Su; Byun, Sei-Hee; Hwang, Sung-Uk; Noh, Kyung-Eun; Park, Yunok; Lee, Jongwon; et al.
ABSTRACT: Dendritic cells (DCs) are the most potent professional antigen (Ag)‐presenting cells and inducers of T cell‐mediated immunity. A previous microarray analysis identified PDZ and LIM domain protein 4 (Pdlim4) as a candidate marker for DC maturation. The aim of this study was to investigate whether Pdlim4 influences DC migration and maturation. Mouse bone marrow‐derived DCs were transduced lentivirally with Pdlim4 short hairpin RNA and examined by confocal microscopy, flow cytometry, ELISA, and Western blotting. Pdlim4 was highly induced in LPS‐stimulated mature DCs (mDCs). Pdlim4 ‐knockdown mDCs showed reduced expression of molecules associated with Ag presentation and T‐cell costimulation, reduced cytokine production, and functional defects in their ability to activate T cells. Moreover, Pdlim4 was necessary for mDC migration via C‐C chemokine receptor type 7 (CCR7)‐JNK in in vitro Transwell assays. The importance of Pdlim4 in DC migration was confirmed with an in vivo migration model in which C57BL/6 mice were injected with fluorescently labeled DCs in the footpad and migration to the popliteal lymph nodes was assessed by flow cytometry. Moreover, dendrite formation in mDCs was remarkably attenuated under Pdlim4 knockdown. Taken together, these results demonstrate that Pdlim4 is necessary for DC migration via CCR7‐JNK, dendrite formation, and subsequent development of functional T‐cell responses.—Yoo, J.‐Y., Jung, N.‐C, Lee, J.‐H., Choi, S.‐Y., Choi, H.‐J., Park, S.‐Y., Jang, J.‐S., Byun, S.‐H., Hwang, S.‐U., Noh, K.‐E., Park, Y., Lee, J., Song, J.‐Y., Seo, H. G., Lee, H. S., Lim, D.‐S. Pdlim4 is essential for CCR7‐JNK‐mediated dendritic cell migration and F‐actin‐related dendrite formation. FASEB J. 33, 11035–11044 (2019). www.fasebj.org